Game day : meet the people who make it happen - Sylvester, Kevin (Annick Press, 2010)
Profiles twenty individuals who, while not professional athletes themselves, work to keep the sports industry running for the players and fans, including a baseball park groundskeeper, a Zamboni driver, and a cameraman.